IoT, machine learning and blockchain technologies for renewable energy and modern hybrid power systems - Sharmeela, C.; Sanjeevikumar, Padmanaban, 1978-; Sivaraman, P.; Joseph, Meera (River Publishers series in computing and information science and technology., 2022)
This edited book comprises chapters that describe the IoT, machine learning, and blockchain technologies for renewable energy and modern hybrid power systems with simulation examples and case studies. After reading this book, users will understand recent technologies such as IoT, machine learning techniques, and blockchain technologies and the application of these technologies to renewable energy resources and modern hybrid power systems through simulation examples and case studies.